2019
DOI: 10.2463/mrms.mp.2017-0136
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast-enhanced T<sub>1</sub> Mapping of Dilated Cardiomyopathy: Comparison between Native T<sub>1</sub> Values and Late Gadolinium Enhancement

Abstract: Non-contrast-enhanced T mapping can be used for assessment of myocardial fibrosis associated with DCM by using the appropriate threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Late gadolinium enhancement is valuable for diagnosis and risk stratification of dilated cardiomyopathy. 3 Recently, Yanagisawa et al 6 have shown that native T 1 mapping is able to depict the myocardial scarring without gadolinium injection. T 1 mapping is also useful for detecting diffuse myocardial fibrosis associated with dilated cardiomyopathy ( Fig.…”
Section: Clinical Application and Relevance Of Quantitative Myocardial Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Late gadolinium enhancement is valuable for diagnosis and risk stratification of dilated cardiomyopathy. 3 Recently, Yanagisawa et al 6 have shown that native T 1 mapping is able to depict the myocardial scarring without gadolinium injection. T 1 mapping is also useful for detecting diffuse myocardial fibrosis associated with dilated cardiomyopathy ( Fig.…”
Section: Clinical Application and Relevance Of Quantitative Myocardial Tmentioning
confidence: 99%
“…[1][2][3] LGE MRI provides binary contrast between scarred and unscarred tissues, while T 1 mapping is complementary to LGE because it can quantify the degree of myocardial fibrosis or edema. [4][5][6] As such, T 1 -weighted imaging techniques, including LGE using an inversion recovery sequence, contribute to cardiac MRI. Conversely, T 2 -weighted imaging is widely used for identification of the pathological status in many organs, because T 2 values are correlated with edema, cellular proliferation, and vessel densities.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular volume fraction (ECV) or native T 1 value measurement is used to overcome this issue. [4][5][6][7][8] These quantitative MRI methods identify diffuse interstitial fibrosis related to hospitalization caused by heart failure, interstitial expansion associated with amyloidosis, and myocardial…”
Section: Introductionmentioning
confidence: 99%
“… 4 8 An important advantage of native T 1 mapping over LGE and ECV measurements is that no gadolinium-based contrast agents are needed. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation